Lingual schwannoma of submandibular region - a unique case in a rare location: a case report and literature review - Seigell, Sunakshi; Gulati, Ankit; Panchal, Vineet; Singla, Priyanka (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Schwannomas are uncommon benign nerve sheath tumors that rarely arise in the oral cavity. Among those found in the oral cavity, tongue is the predominant site of involvement. Lingual schwannomas originating in the submandibular region are exceptionally rare and pose a challenge in diagnosis owing to their nonspecific presentation and resemblance to salivary gland pathologies. Authors report the case of a 15-year-old girl presenting with a two-year history of a painless, progressively enlarging swelling in the left submandibular region, initially suspected to be a submandibular gland lesion. Radiological evaluation with ultrasonography and contrast-enhanced MRI demonstrated a well-defined, lobulated mass adjacent to the gland. The patient underwent surgical excision via a transcervical approach, that revealed the tumor arising from the lingual nerve near the submandibular ganglion. Histopathological examination confirmed the diagnosis of schwannoma, characterized by biphasic Antoni A and Antoni B areas with nuclear palisading. A literature review revealed 125 reported cases of lingual schwannomas, with no gender predilection and a wide age range. Given their infrequent and varied clinical presentation, it is emphasized that lingual schwannomas be considered in the differential diagnosis of submandibular and tongue-associated swellings. Complete surgical excision remains the treatment of choice and offers an excellent prognosis with minimal recurrence risk.